A coordinated effort to manage soybean rust in North America: a success story in soybean disease monitoring - Sikora, E. J.; Allen, T. W.; Wise, K. A.; Bergstrom, G.; Bradley, C. A.; Bond, J.; Brown-Rytlewski, D.; Chilvers, M.; Damicone, J.; DeWolf, Erick; Dorrance, A.; Dufault, N.; et al. (My University, 2014)
Existing crop monitoring programs determine the incidence and distribution of plant diseases and pathogens and assess the damage caused within a crop production region. These programs have traditionally used observed or predicted disease and pathogen data and environmental information to prescribe management practices that minimize crop loss. Monitoring programs are especially important for crops with broad geographic distribution or for diseases that can cause rapid and great economic losses. Successful monitoring programs have been developed for several plant diseases, including downy mildew of cucurbits, Fusarium head blight of wheat, potato late blight, and rusts of cereal crops. A recent example of a successful disease-monitoring program for an economically important crop is the soybean rust (SBR) monitoring effort within North America. SBR, caused by the fungus Phakopsora pachyrhizi, was first identified in the continental United States in November 2004. SBR causes moderate to severe yield losses globally. The fungus produces foliar lesions on soybean (Glycine max) and other legume hosts. P. pachyrhizi diverts nutrients from the host to its own growth and reproduction. The lesions also reduce photosynthetic area. Uredinia rupture the host epidermis and diminish stomatal regulation of transpiration to cause tissue desiccation and premature defoliation. Severe soybean yield losses can occur if plants defoliate during the mid-reproductive growth stages. The rapid response to the threat of SBR in North America resulted in an unprecedented amount of information dissemination and the development of a real-time, publicly available monitoring and prediction system known as the Soybean Rust-Pest Information Platform for Extension and Education (SBR-PIPE). The objectives of this article are (i) to highlight the successful response effort to SBR in North America, and (ii) to introduce researchers to the quantity and type of data generated by SBR-PIPE. Data from this system may now be used to answer questions about the biology, ecology, and epidemiology of an important pathogen and disease of soybean.
Citation: Sikora, E.J., . . . & Zidek, J. (2014). A Coordinated Effort to Manage Soybean Rust in North America: A Success Story in Soybean Disease Monitoring. Plant Disease, 98(7), 864-875. https://doi.org/10.1094/PDIS-02-14-0121-FE
Keywords: Soybean rust; Crop monitoring; Phakopsora pachyrhizi Sydow